AI Rewrites Coding: Even as software grows increasingly complex, artificial intelligence helps to simplify and automate coding tasks. - Greengard, Samuel (Communications of the ACM, 2023)
The article reports on how artificial intelligence (AI) can help to automate and simplify computer coding tasks. Topics include the development of coding tools CodeWhisperer by Amazon, Copilot by GitHub, and Project Wisdom by IBM, as well as the AI-generated code from OpenAI Codex, and how these programs use large language models (LLMs).